An eco-friendly synthesis, characterization and antibacterial applications of novel almond gum – poly(acrylamide) based hydrogel silver nanocomposite. (September 2017) - Syed Ahamed Hussain, I.; Jaisankar, V.
Abstract: Polysaccharide based semi interpenetrating hydrogel (SIH) networks of cross-linked poly(acrylamide) was synthesised through an redox initiating free radical polymerization utilizing almond gum as a grafting backbone, N, N′– methylenebisacrylamide (MBA) as the cross-linker and ammonium persulphate (APS) – N, N, N′, N′-tetramethyl ethylenediamine (TEMED) as the redox initiator pair. Silver ions were introduced into the hydrogel matrix and silver nanoparticles of invariable size were developed insitu of the swollen hydrogel by the reduction of silver ions (Ag + ) using azadirachta indica (neem) leaf extract. The prepared hydrogel - silver nanocomposite (HSN) was characterized by UV–visible diffused reflectance spectroscopy (DRS), fourier transform infrared spectroscopy (FT-IR), high resolution scanning electron microscopy (HR-SEM), energy dispersive X-ray analysis (EDX) and thermogravimetric analysis (TGA). The influence of pH on the swelling behavior of HSN was studied and the antibacterial activity of the developed nanocomposite was evaluated. Highlights: Hydrogel was synthesised in a shortest time via : free radical polymerization. Silver ions were incorporated and converted to nanosilver using green stabilizers. Swelling characteristics were studied and hydrogel silver nanocomposite showed greater swelling. The hydrogel silver nanocomposite showed enhanced antibacterial activity.